2016
DOI: 10.5588/ijtld.16.0342
|View full text |Cite
|
Sign up to set email alerts
|

Blood and urine inducible protein 10 as potential markers of disease activity

Abstract: These findings suggest that IP-10 could be used as a biomarker for disease activity (inflammation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…In this study we showed for the first time that IP-10 agonist and antagonist forms may be detected in urine. In line with our and other publications (Cannas et al, 2010;Petrone et al, 2015;Petrone et al, 2016), we confirmed that IP-10 is increased in the urine of patients with active TB but also in diseases different from TB such as pneumonia. Moreover, we demonstrated that levels of agonist Figure 1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study we showed for the first time that IP-10 agonist and antagonist forms may be detected in urine. In line with our and other publications (Cannas et al, 2010;Petrone et al, 2015;Petrone et al, 2016), we confirmed that IP-10 is increased in the urine of patients with active TB but also in diseases different from TB such as pneumonia. Moreover, we demonstrated that levels of agonist Figure 1.…”
Section: Discussionsupporting
confidence: 93%
“…IP-10 may be released by infected alveolar macrophages promoting the migration of Th1 cells to the site of infection (Kaufmann and Dorhoi, 2013;Lindestam Arlehamn et al, 2013;Moguche et al, 2017;O'Garra et al, 2013;Saha et al, 2013) through binding to CXCR3 expressed on T cells. Moreover, IP-10 is increased in plasma and urine of active TB patients (Goletti et al, 2010a;Goletti et al, 2010b;Vanini et al, 2012) and decreases after efficacious therapy (Azzurri et al, 2005;Chegou et al, 2013;Cannas et al, 2010), correlates with risk of progression to disease and TB disease severity (Azzurri et al, 2005;Petrone et al, 2018;Riou et al, 2012) and is easily detected as an inflammatory marker in both adults and children (Petrone et al, 2015;Petrone et al, 2016;Santos et al, 2018). Importantly, IP-10 is a key player in trained immunity, a protection phenomenon dependent on epigenetic modifications of monocytes (Joosten et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, IP‐10 was also detected in the urine of adult patients and Ugandan children with active TB, and IP‐10 levels decreased following efficacious therapy . As has been recently suggested, however, IP‐10 should probably be considered as a marker of general inflammation …”
Section: Bm For Diagnosing Active Tbmentioning
confidence: 76%
“…22 As has been recently suggested, however, IP-10 should probably be considered as a marker of general inflammation. 51,52 As mentioned above, the use of urine or saliva offers the advantage of noninvasive and ease to handle sampling. It has been reported that saliva levels of interleukin (IL)-1β, IL-23, ECM-1, HCC1 and fibrinogen are significantly associated with active TB.…”
Section: Bm For Diagnosing Active Tb: Immune Protein Host Signatures mentioning
confidence: 99%
“…Our results cannot be generalized to the testing of HIV-infected children, in whom the assay has unfortunately not been found to have utility [34]. Ongoing research on pathogen and host diagnostic urine biomarkers for TB may yield urine assays with improved performance characteristics in the future [3537]. …”
Section: Discussionmentioning
confidence: 99%